2021
DOI: 10.17306/j.jard.2021.01391
|View full text |Cite
|
Sign up to set email alerts
|

Production efficiency of major crops among smallholder farmers in Central Ethiopia

Abstract: Agricultural production of most smallholders in Ethiopia is dependent with recurrent rainfall resulted in production variations. Limited input availability and precarious environmental conditions determine smallholders’ decisions on their production and the production efficiencies vary from farmer to farmer. This study was carried out with the aim of analyzing the technical, allocative and economic efficiencies of smallholder farmers in the production of major crops and their determinants in central Ethiopia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…However, outcomes were erratic. Some have revealed low MTE with a value of 0.48 (Eskeziaw et al, 2021), while others have revealed high MTE with a score of 0.858 (Jeilan Husen and Fentaw, 2019). Evidently, depending on a number of parameters, including the methodology employed, the kinds of data used, the range, the sample size used, and the state or region where the studies are conducted, the empirical estimations of the study's technical efficiency would differ.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcomes were erratic. Some have revealed low MTE with a value of 0.48 (Eskeziaw et al, 2021), while others have revealed high MTE with a score of 0.858 (Jeilan Husen and Fentaw, 2019). Evidently, depending on a number of parameters, including the methodology employed, the kinds of data used, the range, the sample size used, and the state or region where the studies are conducted, the empirical estimations of the study's technical efficiency would differ.…”
Section: Introductionmentioning
confidence: 99%